Ciao! Ciao! Pagsusuri sa mga Pananda ng Negosasyon sa Pagbuo ng Transnasyonal na Identidad ng mga Pilipino sa Venezia, Itaalya / Ciao! Ciao! : Analysis of Signs of Negotiations in the Formation of Transnational Identity of Filipinos in Venice, Italy - Madula, Rowell D. (Malay, 2015)
A number of Filipino families see migration to another country as one of a few means to achieve social mobility. In the past decades, the government's labor export policy to synthesize the resercher's experience during his integration with a Filipino community in Venice, Italy while teaching Filipino language and culture to migrant children and youth. The focus has pushed many Filipinos to find jobs overseas. This paper aims is to identify signs that these Filipinos negotiate their identity in a foreign land. Using the concept of transnational migration, this paper finds out that Filipinos in Venice, Italy negotiate to maintain their Filipino identity while living and integrating with Italian society.